Antiplatelet Resistance and Thromboembolic Complications in Neurointerventional Procedures - Oxley, Thomas J.; Dowling, Richard J.; Davis, Stephen M.; Yan, Bernard; Mitchell, Peter J. (Frontiers in Neurology, 2011)
Antiplatelet resistance is emerging as significant factor in effective secondary stroke prevention. Prevalence of aspirin and clopidogrel resistance is dependent upon laboratory test and remains contentious. Large studies in cardiovascular disease populations have demonstrated worse ischemic outcomes in patients with antiplatelet resistance, particularly in patients with coronary stents. Thromboembolism is a complication of neurointerventional procedures that leads to stroke. Stroke rates related to aneurysm coiling range from 2 to 10% and may be higher when considering silent ischemia. Stroke associated with carotid stenting is a major cause of morbidity. Antiplatelet use in the periprocedure setting varies among different centers. No guidelines exist for use of antiplatelet regimens in neurointerventional procedures. Incidence of stroke in patients post procedure may be partly explained by resistance to antiplatelet agents. Further research is required to establish the incidence of stroke in patients with antiplatelet resistance undergoing neurointerventional procedures